The effect of white‐tailed deer browsing on wheat quality and yields in Delaware - Matthew T. Springer; Jacob L. Bowman; Bruce L. Vasilas (Wildlife Society Bulletin)
Abstract Locally overabundant white‐tailed deer (Odocoileus virginianus; hereafter, deer) have caused increased damage to agronomic crops across their range. Winter wheat (Triticum aestivum) is grown in >60% of the states in the United States where white‐tailed deer occur. Although the effect of deer browsing on corn (Zea mays) and soybean (Glycine max) yields has been documented, research on the effect of deer browsing on winter wheat yields and quality is limited. In 2007–2009, we investigated the effect of deer browse timing and wheat type (bearded and unbearded) on yields and quality in Delaware, USA. We randomly stratified 3 treatments (i.e., no protection, protected at planting, or protected prior to heading) in 1,680 plots. After head emergence, we surveyed the plots weekly to estimate browse rates and biomass removed by deer. We harvested a 1‐m2 area in the middle of each plot to determine the deer impact on yield. Browsing increased in intensity as head development progressed and more browsing occurring on the unbearded wheat. Unprotected plots had 195 kg/ha greater wheat yield than did protected plots in 2007 (P = 0.08). We found no difference in wheat yield among treatments during 2008 and 2009 (P = 0.38). Bearded wheat fields had 379 kg/ha greater wheat yield during 2007 and 399 kg/ha greater yield during 2008 and 2009 than did unbearded wheat fields (P < 0.001). We also observed no difference in wheat quality among treatments or between types of wheat (P > 0.417). Our browse surveys suggested avoidance of bearded wheat but the overall browsing was not intense enough to affect yield. Our results demonstrated that white‐tailed deer had no impact on wheat yield at a deer density of 15 deer/km2. © 2013 The Wildlife Society.